ANALISIS VARIABEL ANTESEDEN BRAND EQUITY DAN HUBUNGANNYA TERHADAP PURCHASE DECISION - Putra, Achmada; Rahardjo, Susilo Toto (Diponegoro Journal of Management, 2016)
Globalization has encouraged businesses to expand into various countries, TOP 1 Oil as a product of American origin was present to Indonesian automotive industry. However, competition with domestic products have made the motor TOP 1 Oil has percentage decreasing of top brand index (TBI) consecutively in 2012 to 2015. This is supported by the decline in sales of motor TOP 1 Oil especially in Semarang.The purpose of this study is to determine the influence of variables country of origin image, marketing capabilities, and perceived quality towards brand equity, this correlation are expected can increase sales of TOP 1 Oil. Variable country of origin image, marketing capabilities, and perceived quality of is a reference as an independent variable. Brand Equity as an intervening variable and Purchase Decision as the dependent variable.The population used in this research is the consumer of TOP 1 Oil. This research method using a non-probability sampling technique with convenience sampling method. Used as a sample of 150 respondents. Data obtained from the questionnaire which is then processed and analyzed using SEM (Structural Equation Modeling) through AMOS program.The results showed that all three of independent variable has a positive influence on brand equity and brand equity has a positive influence on the purchase decision. From the influence of three independent variables, the country of origin image has the greatest impact on brand equity and then followed with the marketing capabilities and the smallest is the perceived quality.